The Assessment of Deforestation Impact Towards Microclimate and Environment in Ilorin, Nigeria - Toluwalope Mubo Agaja; Elisha Ademola Adeleke; Enekole Esther Adeniyi; Precious Temilade Afolayan (Department of Geography Education, University of Jember, 2020)
Nigeria obtains high rate of deforestation with a loss of about 60 percent of its primary forests between 2000 and 2005 as a result of logging, subsistence agriculture, wood exploitation, and urban expansion.This research assessed the level of deforestation and how it has affected Ilorin’s microclimate and the environments. The specific objectives of this study were assessing the relationship that occurs between deforestation and microclimate, examining deforestation and the impact it has within the study area of microclimate, and forecasting the microclimate within the study area by the year 2030. The statistical tools engaged were both descriptive (mean, frequency distribution table and, bar charts) and inferential statistics (multiple regression analysis). The research indicated that there is a significant relationship between deforestation with r2 variables of 0.888 for maximum temperature, 0.201 for minimum temperature, 0.997 for precipitation, 0.43 for solar output, -0.797 and -0.873 for evapotranspiration and relative humidity respectively and Ilorin’s microclimate. The study concludes that deforestation greatly influences the microclimate of Ilorin and occurs due to human’s anthropogenic activities. Deforestation has also led to climate change. Keywords: Deforestation; Climate; Micro-climate; Vegetation Cover Copyright (c) 2020 Geosfera Indonesia Journal and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License